MANAJEMEN PENANGGULANGAN BENCANA BANJIR OLEH BADAN PENAGGULANGAN BENCANA DAERAH (BPBD) DI KABUPATEN PATI - Rohman, Satria Nur; Lituhayu, Dyah; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Pati Regency ranks 95 out of 394 cities or districts for flood disasters. This proves that the highest natural disaster threat, as well as the most vulnerable one in Pati District, is flood alarms that often occur during the rainy season every year. During the years 2020–2022, flood disasters in Pati District continued to increase, both in terms of the affected area, the depth of water, and the duration of the water receding. Up to this point, the Regional Disaster Management Agency of Pati District, as a department responsible for addressing the phenomenon of floods, continues to strive to mitigate these occurrences. The purpose of this study is to describe and identify the supporting and inhibiting factors of the Regional Disaster Management Agency of Pati District in flood disaster management. The research method used is qualitative descriptive using management theory, according to George R. Terry in Harsuki 2012, p. 79. Based on the disaster management conducted, several functions have been well executed, including planning, organizing, and mobilizing. The implementation of flood disaster management is carried out collaboratively with local departments, stakeholders, and volunteers. However, there are obstacles in the supervision function, namely the lack of scheduled organizational performance evaluations. Other obstacles include a lack of facilities, personnel, and budget for the Regional Disaster Management Agency of Pati District.